Educators' occupational well-being in health and social care education - Rinne Jenni; Leino-Kilpi Helena; Saaranen Terhi; Pasanen Miko; Salminen Leena (OXFORD UNIV PRESS, 2022)
Background
The occupational well-being (OW) of educators can be defined as a balance between resources and workload factors as seen from four aspects of working life: (i) individual, (ii) working conditions, (iii) professional competence and (iv) work community. The research in this study examined the individual aspect as particular importance to the physical and mental workability of educators.
Aims
To study the individual aspect of the OW of educators as well as the associating factors.
Methods
A cross-sectional survey design was conducted among educators working in health and social care education in Finland. The data were collected with an electronic survey using the 'Occupational well-being of social and health care teachers-index questionnaire'. The data were analysed with an SPSS version 27 using descriptive statistics, explorative factor analysis and linear regression analysis.
Results
The educators (n = 552, response rate 31%) assessed their resources for managing their mental workload as quite poor (2.41, standard deviation [SD] 0.98). In addition, workplace support promoting OW was assessed as being quite poor (2.37, SD 0.88), and as especially requiring more measures during working hours. Associations with the individual aspect of OW were found between the personal and work-related background variables as well as overall OW.
Conclusions
The perceptions of the educators indicated that resources to cope with workload factors should be promoted. Investing in educators' resources at work, enabling well-being actions during working hours and avoiding backlog situations would all help promote the educators' OW.